Visual Narratives of Trauma: Analyzing Paintings by Child Survivors of the 2018 Palu Liquefaction Disaster - I Made Fenggi Andreana; Yun Ratna Lagandesa; Kadek Hariana; Rizal Rizal (Journal of Innovation and Research in Primary Education, 2026)
Children survivors of the 2018 Palu liquefaction disaster experienced profound psychological trauma that often exceeds verbal articulation capacity. Visual art provides alternative pathways for understanding children's disaster experiences and psychological states. This study examined visual characteristics in paintings produced by child liquefaction survivors at SDN 1 Petobo to understand how children represent traumatic disaster experiences through artistic expression. A qualitative descriptive design was employed with purposive sampling of child survivors aged 7-12 years. Data collection involved systematic analysis of children's paintings, semi-structured interviews with children, teachers, and parents, and observational documentation. Visual characteristics were analyzed using Miles and Huberman's interactive model, focusing on line quality, spatial organization, symbolic elements, form, and color selection. Triangulation across multiple data sources ensured trustworthiness. Analysis revealed consistent patterns: irregular, broken lines depicted environmental instability; cross-sectional spatial representations demonstrated internalization of liquefaction mechanics; universal inclusion of displaced structures and endangered figures established shared trauma narrative; dark earth tones dominated disaster zones while bright colors in peripheral spaces suggested preserved hope. Notably, rescue personnel were absent from all paintings, indicating ongoing vulnerability perceptions. Children's post-disaster artwork functions as multilayered text encoding traumatic experience, scientific understanding, and psychological states simultaneously. Findings validate art-based approaches for trauma assessment and support integration of creative expression into disaster education curricula.